Computational Study of Cresyl Violet Covalently Attached to the Silane Coupling Agents: Application to TiO2-Based Photocatalysts and Dye-Sensitized Solar Cells - Tatsuya Takeshita (Nanomaterials, 2020)
The covalent attachment of photosensitizing dyes to TiO2 using silane coupling agents (SCAs) is a promising strategy for enhancing the photocatalytic activity of TiO2-based photocatalysts and the photovoltaic conversion of dye-sensitized solar cells (DSSCs). This approach can control the geometry and orientation of the photosensitizing dye on the TiO2 surface. In this study, a density functional theory (DFT) and time-dependent DFT (TD-DFT) investigation was carried out on cresyl violet (CV) covalently attached to SCAs with a terminal oxirane group (OTES–Cn) to reveal the influence of OTES–Cn on the geometry of the photosensitizing dyes. The potential of CV covalently attached to OTES–Cn (CV–OTES–Cn) to act as a photosensitizing dye was also analyzed. The hydroxyl group formed by the epoxy-opening reaction between CV and OTES–Cn strongly influenced the geometry of CV–OTES–Cn, which was attributed to a CH–O interaction. Additionally, TD-DFT, frontier molecular orbital and molecular electrostatic potential calculations revealed that CV–OTES–Cn has excellent optical properties and electron injection ability. In particular, the characteristics of the unbent conformation of CV–OTES–Cn are expected to contribute significantly to the photocurrent in TiO2-based photocatalysts and DSSCs. These findings enhance the understanding of the covalent attachment strategy using SCAs and contribute to improving TiO2-based photocatalysts and DSSCs.